A Case Study of Using an Object-Relational Paradigm in Building a Web Database Application - Rahayu, J. Wenny; Taniar, David; Lee, Nung Kion; Pardede, Eric (International Society for Computers and Their Applications (ISCA), 2003)
In this paper, we would like to share our experiences in building a web database application using an object-relational paradigm. The system we built is basically an online system for casual tutors to claim their work for payment. At the design stage, we use an object-oriented design. Since the database backend is a relational database management system (i.e. Oracle), which also supports some object-oriented features, we need to apply a transformation methodology to map our object-oriented design into relational tables incorporating some object features in Oracle. Once the necessary object types and tables have been created, at the programming stage we use a PHP scripting language accessing the Oracle database where the data is stored.